Impact of dc-sputtered mo interlayer on the structural and compositional properties of cu2znsns4 (CZTS) thin films on flexible mo substrates - Heriche H.; Chelvanathan P.; Shahahmadi S.A.; Yusoff Y.; Bais B.; Rouabah Z.; Tiong S.K.; Sopian K.; Amin N. (S.C. Virtual Company of Phisics S.R.L, 2023)
In this paper, a comprehensive study on the structural and compositional properties of sulfurized Cu2ZnSnS4 (CZTS) thin film is presented to elucidate technological challenges of fabrication on flexible Mo substrates. At first, CZTS thin films were deposited by RF sputtering technique on bare flexible molybdenum foil (Mo-foil) as well as on the Mo-foil with DC-sputtered Mo thin film layer (Mo thin film/Mo-foil). Then, samples were annealed in the presence of sulfur (S) and tin (Sn) powder from 550C to 580C. The results from XRD showed advantages of Mo thin film/Mo-foil over its counterpart in terms of peak intensity and overall structural quality. The existence of dominant (112) peak, which confirms the polycrystalline structure for all CZTS samples was observed. Compositional analysis was carried out by EDX and it was found that the atomic ratio for CZTS thin films on the Mo thin film/Mo-foil is prone to be Cu-poor and Zn-rich with the average value of 0.84 and 1.12, respectively. Therefore, Mo thin film/Mo-foil bilayer structure has been identified as a more suitable substrate configuration compared to bare Mo-foil for CZTS thin films. 2019, S.C. Virtual Company of Phisics S.R.L. All rights reserved.